UPAYA HUKUM PENINJAUAN KEMBALI DALAM PERKARA PIDANA PASCA PUTUSAN MAHKAMAH KONSTITUSI - Harsanto, Adi (Katalogis, 2017)
It was a juridical normative (legal) research studying the standing of Article 268 Section (3) of Law Number: 8 Year 1981 prior to and post Constitutional Court Verdict, Number: 34/PUU-XI/2013 and the attempts for Judicial Review to Constitutional Court Verdict, Number: 34/PUU-XI/2013 under perspectives of justice principle, benefit principle and certainty principle. A judicial review in a criminal case is an extra-ordinary legal attempt taken by a prisoner against a court verdict legally binding, on condition that there have been mistakes by the judge sentencing the verdict and there is a new novum never before presented in the trials. The judicial review as provided under Article 268 Section (3) of the Indonesian Criminal Codes rules that a judicial review may be filed only once. On the other hands, the Constitutional Court Verdict, Number : 34/PUU-XI/2013 provides that judicial reviews may be filed time to time in search of legalÂ material justice. In short, Article 268 Section (3) of the Indonesian Criminal Codes is superseded as it is not consistent with the Indonesian Constitution (UUD 1945). The effect ofÂ a constitutional law in a criminal case is conflicting with Article 24 Section (2) of Law Number : 48 Year 2009 about Judicial PowerÂ and Article 66 Section (1) of Law Number : 14 Year 1985 about Supreme Court as amended with Law Number : 5 Year 2004 and 2nd Amendment to Law Number : 3 Year 2009, as well as Circular of Supreme Court Number: 7 Year 2014 principally confirming that a judicial review may be filed only once to secure a legal certainty. The Constitutional Court Verdict, Number: 34/PUU-XI/2013 is not to destruct a legal certainty. A legal certainty is attain when a verdict is already legally binding and has changed the status of an accused into a prisoner as confirmed in Article 268 Section (1) of the Indonesian Criminal Codes. The principles of justice and legal certainty are inconsistent with multiple judicial reviews, as the later leads to a legal uncertainty to someone.